Anti-Escherichia Coli 0157 : H7 And Anti-Oxidant Activities Of Acetone Extract Of Piper Betle L. And Its Fractions - Ismail, Nur Sharafina (2014)
E. coli 0157:H7 is a newly emerging pathogen that cause bloody diarrhoea to severe abdominal cramps, haemolytic uremic syndrome (HUS), thrombotic thrombocytopenic purpura and even death. There are reports that antibiotic treatment increases the risk of patients developing fatal HUS. Therefore plant products could be an alternative source for prevention of transmission and hence infection of the pathogen among the general populations. By disc diffusion assay, out of twenty four extracts from eight Malaysian plants, acetone extract of P. betle inhibited E. coli 0157:H7 strongly giving the largest inhibition zone at 20.56 ± 0.19 mm. This correlates strongly with its total phenolic content (TPC) which was the highest among those tested at 430.69 ± 47.50 μg GAE/ mg as determined by Folin-Ciocalteu method. By microdilution assay, acetone extract of P. betle gave the lowest MIC at 500 μg/ ml and MBC at 2000 μg/ ml against E. coli O157:H7. Bio-assay guided fractionation of acetone extract was done using a solvent system of chloroform: methanol at a ratio of 19:1. Fractionation was done by preparative TLC and the fractions collected were all assessed for antibacterial activity, TPC and AOA. Fraction 5 gave the lowest MIC against E. coli 0157:H7 at 500 μg/ ml, high TPC (398.25 ± 7.74) as well as high anti-oxidant activity as assessed by DPPH (80.43 ± 0. 71 %). Upon storage, the antibacterial activity of fraction 5 was reduced. It was subsequently mixed with fraction 6 and 7 (now known as Fraction A) which was more stable. The MIC for fraction A against E. coli O157:H7 was much lower at 250 μg/ml but its MBC increased to >2000 μg/ ml. Acetone extract of P. betle and fraction A were also tested for induction of morphological and ultrastructural changes of E. coli O157:H7 at exponential phase in a batch culture. Based on observation by SEM and TEM, cellular damage by fraction A was not as severe as that given by acetone extract, both at 2000 μg/ml. Toxicity assay using brine shrimp (Artemia salina) showed LC50 of acetone extract was 500 μg/ ml and fraction A was >1000 μg/ ml. Gas chromatography- mass spectrometry (GC-MS) of the fraction revealed three major phenolic compounds, Chavicol, Hydroxychavicol and Chavibetol which may contribute to the antibacterial activity. From this study, it can be concluded that fraction A at 250 μg/ ml to 2000 μg/ ml and acetone extract up to 500 μg/ ml were only bacteriostatic towards E. coli O157:H7 meanwhile acetone extract was bactericidal at 2000 μg/ ml. Acetone extract was toxic at bactericidal concentration, while fraction A though bacteriostatic was non-toxic.